Murder on the VR Express: Studying the Impact of Thought Experiments at a Distance in Virtual Reality - Andrew Kissel; Krzysztof J. Rechowicz; John B. Shull (Societies, 2023)
Hypothetical thought experiments allow researchers to gain insights into widespread moral intuitions and provide opportunities for individuals to explore their moral commitments. Previous thought experiment studies in virtual reality (VR) required participants to come to an on-site laboratory, which possibly restricted the study population, introduced an observer effect, and made internal reflection on the participants’ part more difficult. These shortcomings are particularly crucial today, as results from such studies are increasingly impacting the development of artificial intelligence systems, self-driving cars, and other technologies. This paper explores the viability of deploying thought experiments in commercially available in-home VR headsets. We conducted a study that presented the trolley problem, a life-and-death moral dilemma, through SideQuestVR, a third-party website and community that facilitates loading applications onto Oculus headsets. Thirty-three individuals were presented with one of two dilemmas: (1) a decision to save five lives at the cost of one life by pulling a switch and (2) a decision to save five lives at the cost of one life by pushing a person onto train tracks. The results were consistent with those of previous VR studies, suggesting that a “VR-at-a-distance” approach to thought experiments has a promising future while indicating lessons for future research.